Constable & Toop - Jones, Gareth P. (Laura Ann); 1978- 1906-1998. 1952- 1974- (New York Amulet Books, 2013)
In Victorian London, an undertaker's son who can see ghosts and is haunted by their constant demands for attention must decide whether to help when a horrible disease imprisons ghosts into empty houses in the world of the living.
Originally published in London by Hot Key Books, 2012.
Keywords: Ghosts -- Fiction; Future life -- Fiction; History -- Fiction. -- 19th century -- London (England); History -- Fiction. -- Victoria, 1837-1901 -- Great Britain; New York (N.Y.)